2005
DOI: 10.2903/j.efsa.2005.175
|View full text |Cite
|
Sign up to set email alerts
|

Opinion of the Scientific Panel on biological hazards (BIOHAZ) on Bacillus cereus and other Bacillus spp in foodstuffs

Abstract: SUMMARYBacillus cereus is the cause of two kinds of foodborne diseases, an emetic (vomiting) intoxication due to the ingestion of a toxin (cereulide) pre-formed in the food and a diarrhoeal infection due to the ingestion of bacterial cells/spores which produce enterotoxins in the small intestine. Other Bacillus spp., B. subtilis, B. licheniformis, B. pumilus have more rarely beeen identified as agents of foodborne diseases characterized by diarrhoea and/or vomiting. Emetic intoxication is caused by a very homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 115 publications
0
26
0
Order By: Relevance
“…Bacillus cereus B. cereus is ubiquitous in nature, commonly found in soil and associated with improper food handling/storage, and improper cooling of cooked foods [28]. B. cereus causes two types of foodborne illness, an emetic (vomiting) intoxication due to the ingestion of a toxin (cereulide) pre-formed in the food and a diarrheal infection due to the ingestion of bacterial cells/spores which produce enterotoxins in the small intestine [42]. More recently, the European Food Safety Authority (EFSA) panel on biological hazards (BIOHAZ) [43] reported that most cases of foodborne diseases have been associated with greater than 10 5 CFU/g of B. cereus in the food vehicle, with some cases ranging to 10 8 CFU/g for diarrheal infection.…”
Section: Selection Of a "Short List" Of Significant Hazardsmentioning
confidence: 99%
“…Bacillus cereus B. cereus is ubiquitous in nature, commonly found in soil and associated with improper food handling/storage, and improper cooling of cooked foods [28]. B. cereus causes two types of foodborne illness, an emetic (vomiting) intoxication due to the ingestion of a toxin (cereulide) pre-formed in the food and a diarrheal infection due to the ingestion of bacterial cells/spores which produce enterotoxins in the small intestine [42]. More recently, the European Food Safety Authority (EFSA) panel on biological hazards (BIOHAZ) [43] reported that most cases of foodborne diseases have been associated with greater than 10 5 CFU/g of B. cereus in the food vehicle, with some cases ranging to 10 8 CFU/g for diarrheal infection.…”
Section: Selection Of a "Short List" Of Significant Hazardsmentioning
confidence: 99%
“…This review focuses on the second form of disease, which is characterized by diarrhea and abdominal pain. The infective dose for this type is estimated from 10 5 -10 8 cfu/g [46,47] or 10 4 -10 9 cfu/g [48] (colony forming units per gram of food) vegetative cells or spores. Responsible for the symptoms are different protein enterotoxins, which form pores in the membranes of epithelial cells in the small intestine.…”
Section: Introductionmentioning
confidence: 99%
“…B. cereus is a Gram-positive, spore-forming bacterium widespread in natural environment [8,9]. It can cause two types of food poisoning in humans, including diarrheal and emetic syndromes, along with a variety of local and systemic infections, such as endophthalmitis, endocarditis, meningitis, osteomyelitis, wound infections, and septicemia [10,11].…”
Section: Introductionmentioning
confidence: 99%